Best $m$-term trigonometric approximation for the classes $B^r_{p,θ}$ of functions of low smoothness - Stasyuk, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain an exact-order estimate for the best $m$-term trigonometric approximation of the Besov classes $B^r_{p,θ}$ of periodic functions of many variables of low smoothness in the space $L_q, \; 1 < p ≤ 2 < q < ∞$.